SILATURRAHMI DALAM PERSPEKTIF SUNNAH (SUATU KAJIAN HADIS MAUDHU’I DENGAN PENDEKATAN ILMU MA’ANI AL-HADIS) - Firdaus Firdaus; Siar Nimah (LP2M IAIM Sinjai, 2026)
Silaturahmi (maintaining family and social ties) is a fundamental teaching in Islam that regulates human and social relations. This article aims to analyze the virtues, positive impacts, and threats of severing silaturahmi from the perspective of the hadiths of Prophet Muhammad ﷺ, while reviewing its relevance to modern scientific findings and its contextualization in the digital era. This study employs a qualitative approach with a descriptive-analytical library research method using a thematic hadith approach (maudhu’i) and the science of ma’ani al-hadis. The results indicate that the Prophet's hadiths consistently emphasize the virtues of silaturahmi, such as expanding sustenance, prolonging life, and gaining Allah's assistance. Scientifically, the meaning of